Penerapan Konsep Wakaf Aset Digital di Indonesia - Uwais, Asnawi; Dedy Rachmad; Afifah, Kuni (Bukhori: Kajian Ekonomi dan Keuangan Islam, 2024)
Purpose: This study aims to determine how Islam views the use of digital assets for waqf and the potential of digital assets in waqf and its scheme. Methodology: This qualitative research uses a library research method to answer the questions raised. Secondary data were used in this study. Results: The results of this study found that the use of cryptocurrency as an asset for waqf is not allowed and only accepts rupiah as a legal tender, while the use of YouTube accounts as a source of waqf is allowed as long as it does not contain elements that are prohibited in Islam. Limitations: Limited literature on digital waqf, especially international literature. The lack of literature makes it difficult to find relevant information and develop a comprehensive understanding of the topic. Contribution: One of the main contributions of this research is that it provides an answer to the question of the lawfulness of using digital assets, according to Islamic law. This is a significant contribution because there is currently a lack of clarity regarding this issue.